Florilegium of Fortunata Obrąpalska – iconography of biological diversity in natural phenomena - Kalinowska, Małgorzata (Biodiversity: Research and Conservation, 2019)
Botanical drawings of Fortunata Obrąpalska are an unknown part of work of this eminent Polish artist photographer. In the special collections of the Library of Botanical Garden of Adam Mickiewicz University in Poznań, there are 523 drawings of Fortunata Obrąpalska that she created in the years 1955-1983. The simple Bristol board ink drawing technique depicts in schematic, but at the same time perfect way, plants and natural phenomena like withering of underground plant organs, frost-damaged shoots or impact of wind on plants in coastal areas. The drawings are a proof of her excellent knowledge of natural objects, impressive drawing skills and imagination. They also show this artist’s great sensitivity to beauty.